2009
DOI: 10.1248/cpb.57.814
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity and DNA-Binding Investigations of the Zn(II) and Cu(II) Complexes with Isoeuxanthone

Abstract: Recently, more and more attention has been paid to xanthones that are widely present as a class of secondary metabolites in some higher plants and microorganisms. [1][2][3] These naturally occurring compounds and their synthetic analogs have been reported to exhibit multiple important pharmacological properties, such as anti-oxidant, anti-inflammatory, anti-malarial and anti-cancer activity, etc. [4][5][6][7][8][9] As shown in Fig. 1a, xanthones having three linear fused aromatic rings may be viewed as flavone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…Such variations are indicative of a likely intercalation mode of the two complexes into ct double helix DNA, most likely similar to that obtained with ethidium bromide, EB (see below). 66 Nevertheless, the association constant between DNA and ethidium bromide is two orders of magnitude higher than the one calculated for our complexes showing that EB is a stronger intercalating agent.…”
Section: Dna-binding Studies By Absorption and Emission Titrationscontrasting
confidence: 63%
“…Such variations are indicative of a likely intercalation mode of the two complexes into ct double helix DNA, most likely similar to that obtained with ethidium bromide, EB (see below). 66 Nevertheless, the association constant between DNA and ethidium bromide is two orders of magnitude higher than the one calculated for our complexes showing that EB is a stronger intercalating agent.…”
Section: Dna-binding Studies By Absorption and Emission Titrationscontrasting
confidence: 63%
“…IC 50 values of 2 and 3 reach about 10 μM, lower than that of some previously reported analogous copper(II) complexes against these human alimentary system carcinoma cell lines [18][19][20][33][34][35][36], indicating that 2 and 3 have potent cytotoxicity.…”
Section: Copper(ii) Complexes 2353mentioning
confidence: 59%
“…Four human alimentary system carcinoma cell lines, SGC7901 (gastric tumor cell line), EC109 (esophagus tumor cell line), SMMC7721 (liver tumor cell line), and HT29 (colon tumor cell line), were utilized in our work. These cell lines were chosen to explore the potential selectivity of our copper(II) complexes towards different human alimentary system carcinoma cell lines and all have been previously used in studies with copper complexes that are cytotoxic [18][19][20][21]. IC 50 values indicated that 2 and 3 have promising cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The mononuclear Cu­(II) complex [Cu­( L 26a ) 2 ] (Figure b) promoted an intercalative interaction with CT-DNA with a calculated binding constant value of 2.5 × 10 4 M –1 . Complex 26a showed a moderate cytotoxic potency toward ECA109 (IC 50 = 20.8 μM) and SGC-7901 (IC 50 = 25.7 μM) cells . Insertion of a pendant piperidinyl-ethoxy group onto the isoeuxanthone moiety did not enhance the biological properties of the corresponding 26b complex (Figure b) …”
Section: Copper Complexes As Anticancer Agentsmentioning
confidence: 96%